2014
DOI: 10.15430/jcp.2014.19.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Endoscopic, Histologic and Serologic Diagnoses for the Assessment of Atrophic Gastritis

Abstract: a total of 2,558 subjects were enrolled. Endoscopic atrophic gastritis was graded by Kimura-Takemoto classification and histological atrophic gastritis was assessed by updated Sydney system. Serological assessment of atrophic gastritis was based on serum pepsinogen test. Results: The serum pepsinogen I/II ratio showed a significant decreasing nature when the extent of atrophy increased (R 2 =0.837, P<0.001) and the cut-off value for distinguishing between presence and absence of endoscopic atrophic gastritis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 27 publications
1
56
0
4
Order By: Relevance
“…For example, the median PGI levels were >90 µg/l in Shandong, China (25), the mean PGI was >100 µg/l in Hunan, China (17) and Yazd, Iran (24), whereas values were usually <70 µg/l in European countries (4,26). However, a Japanese study by Inoue et al (19) involving 200 patients and a Korean study involving 2,558 patients by Lee et al (27) reported a mean serum PGI:I level of <70 µg/l (56.0 and 63.5 µg/l, respectively). Whether these variations in serum PG levels are due to different geographical locations (with ensuing different ethnicities), prevalence of the H. pylori infection, prevalence of CAG and gastric carcinoma or varying dietary patterns remains uncertain and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the median PGI levels were >90 µg/l in Shandong, China (25), the mean PGI was >100 µg/l in Hunan, China (17) and Yazd, Iran (24), whereas values were usually <70 µg/l in European countries (4,26). However, a Japanese study by Inoue et al (19) involving 200 patients and a Korean study involving 2,558 patients by Lee et al (27) reported a mean serum PGI:I level of <70 µg/l (56.0 and 63.5 µg/l, respectively). Whether these variations in serum PG levels are due to different geographical locations (with ensuing different ethnicities), prevalence of the H. pylori infection, prevalence of CAG and gastric carcinoma or varying dietary patterns remains uncertain and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Lee et al [25] revealed PGI and PG I/II ratio decreased significantly as EAB progressed, and we also searched relationships between serology and EAB. Yanaoka et al [2] showed H.pylori eradication was effective for preventing GC only in serologically mild atrophic gastritis, we uncovered which EAB could be matched with upper limit of serologically mild atrophic gastritis, the cut-off value of EAB for group C being above type C-3, this identification was similar to that of several previous studies, however there were differences, first most of previous studies identified serologic values to discriminate open type atrophic gastritis from closed type, we took different approach from opposite side: defining optimal EAB for serologically significant value, second we subdivided EAB in more detail (12 categories) because in Korea endoscopy is more dominant GC screening tool than any other method including serologic study, consequently we need to get much more delicate description for endoscopic findings than just simple delineation of open or closed type.…”
Section: Discussionmentioning
confidence: 94%
“…Sydney system scores express the severity of gastritis at a biopsy point, whereas PG I/II ratio express the spread of mucosal atrophy (16,26). It has been reported that the significant association between serum and histological atrophy is more strongly observed in the corpus compared with in the antrum (27). The present study assessed the histological gastritis only in the antrum, as the antrum is affected by H. pylori infection for the longest period (4).…”
Section: Discussionmentioning
confidence: 99%